2012
DOI: 10.29252/jmj.10.2.57
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the quality and quantity of clinical education from the viewpoint of medical students

Abstract: Introduction: Clinical education is a process during which students gradually acquire skills for clinical management of patients by visiting patients. The aim of this study was to determine the quality and quantity of clinical education from the view point of junior and senior doctors. Materials and Methods: This is a descriptive, analytical study. All clinical students of the faculty of medicine in YUMS in the year 1385-1386 were surveyed after they gave their informed written consent. Data were collected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 6 publications
4
27
0
Order By: Relevance
“…Other issues that have affected clinical education are resource problems and facilities. The results of the present study showed that the necessary infrastructures such as lack of access to the Internet and web-based educational resources (18,21,26), lack of availability and updating of library resources (31,34) and lack of access to educational journals (31) are important things that can lead to student dissatisfaction.…”
Section: Challenges and Problems Of Clinical Medical Education In Iramentioning
confidence: 80%
See 4 more Smart Citations
“…Other issues that have affected clinical education are resource problems and facilities. The results of the present study showed that the necessary infrastructures such as lack of access to the Internet and web-based educational resources (18,21,26), lack of availability and updating of library resources (31,34) and lack of access to educational journals (31) are important things that can lead to student dissatisfaction.…”
Section: Challenges and Problems Of Clinical Medical Education In Iramentioning
confidence: 80%
“…Masic et al in a study in Sarajevo found that students considered the most important factor in improving the quality of medical education as having up-to-date educational facilities (55). On the other hand, lack of physical resources such as inadequate library space (34), insufficient number of computers in hospitals (31) and lack of human resources such as experts and faculty members (26,27,33,37) are among the factors affecting the quality of clinical education.…”
Section: Challenges and Problems Of Clinical Medical Education In Iramentioning
confidence: 99%
See 3 more Smart Citations